Artificial intelligence and security challenges in emerging networks - Abassi, Ryma, 1980- (Engineering Science Reference, 2019)
"This book explores the recent rise of emerging networking technologies such as social networks, content centric networks, IoT networks, etc. It also examines the applications of artificial intelligence (AI), machine learning, and data mining to security and privacy problems"- Resumé vydavatel
Keywords: zabezpečení počítačových sítí; kybernetická bezpečnost; malware; umělá inteligence; computer network security; cyber security; artificial intelligence; electronic books; papers of several authors; sborníky; elektronické knihy